DESCRIÇÃO DAS AÇÕES DE VIGILÂNCIA EM FOCOS DA DOENÇA DE AUJESZKY - Oliveira, Luís Guilherme De; Oliveira, Maria Emilia Franco; Alexandrino, Bruna; Gatto, Igor Renan Honorato; Almeida, Henrique Meiroz De Souza; Samara, Samir Issa (Universidade Federal de Goiás, 2015)
AbstractAujeszky’s disease (AD) is known for causing huge productive and economical losses in the swine industry. This study focused on describing the actions of the official animal health protection used on identification of AD outbreaks. Two outbreaks that occurred in Cerqueira César city were selected, a case presenting only seropositive animals (outbreak 1) and another one where there were animals with clinical signs of the disease (outbreak 2). The methods used to identify the outbreaks in surveillance actions and to diagnose the epidemiological situation were described. The measures implemented to eliminate the outbreaks in infected pig production systems were appointed in animal health protection laws and were able to eliminated all outbreaks identified. In conclusion, the official animal health protection measures and the appliance of the sanitary legislation were effective in eradicating AD, reassuring that notifications of suspicous cases of AD facilitate animal health surveillance activities.

ResumoA doença de Aujeszky (DA) é conhecida na suinocultura pelo seu grande impacto produtivo e econômico. Este trabalho teve como objetivo a descrição das ações de defesa sanitária animal utilizadas na identificação de focos dessa enfermidade. Foram selecionadas duas situações de foco de DA que ocorreram no Município de Cerqueira César, um caso apresentando somente animais sororreagentes (Foco 1) e outro em que havia animais com sinais clínicos da enfermidade (Foco 2). Estão descritos os métodos de identificação de focos utilizados nas ações de vigilância e o diagnóstico da situação epidemiológica encontrada. As medidas aplicadas na erradicação dos focos nos sistemas de produção de suínos infectados foram as prescritas na legislação de defesa sanitária animal e todos os focos identificados foram eliminados. Ao final, concluiu-se que as ações de defesa sanitária e a legislação em vigor foram eficazes, demonstrando que os sistemas de notificações das suspeitas da enfermidade são facilitadores das ações de vigilância.
DESCRIPTION OF SURVEILLANCE ACTIONS IN OUTBREAKS OF AUJESZKY'S DISEASE
Keywords: outbreaks; pig production; sanitary legislation; swine Herpesvirus; focos; Herpesvirus Suíno; legislação sanitária; suinocultura